2019
DOI: 10.1128/jvi.02026-18
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 2 Receptor Expression Is Promoted by Human Herpesvirus 8-Encoded Interleukin-6 and Contributes to Viral Latency and Productive Replication

Abstract: Human herpesvirus 8 (HHV-8) viral interleukin-6 (vIL-6) localizes largely to the endoplasmic reticulum (ER) and here associates functionally with both the gp130 signal transducer and the novel ER membrane protein vitamin K epoxide reductase complex subunit 1 variant-2 (VKORC1v2). The latter interaction contributes to the viability of latently infected primary effusion lymphoma (PEL) cells and to HHV-8 productive replication, in part via promotion of ER-associated degradation (ERAD) of nascent procathepsin D (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“…Among these was the multifunctional receptor IGF2R, a protein involved in intracellular retrograde transport 87 . IGF2R was reported to support the replication of the gamma herpesvirus HHV-8 and the retrovirus HIV-1 88,89 , and our results also establish it as a pro-viral factor during HCMV infection. While the disruption and reduction of IGF2R signal around the nucleus early in infection is consistent with the Golgi reorganization by HCMV 12 , the IGF2R localization to the assembly complex late in infection and the inhibitory effect of its knockout on virus production suggest that HCMV hijacks IGF2R to coordinate cell signaling.…”
Section: Prm Validation Igf2rsupporting
confidence: 79%
“…Among these was the multifunctional receptor IGF2R, a protein involved in intracellular retrograde transport 87 . IGF2R was reported to support the replication of the gamma herpesvirus HHV-8 and the retrovirus HIV-1 88,89 , and our results also establish it as a pro-viral factor during HCMV infection. While the disruption and reduction of IGF2R signal around the nucleus early in infection is consistent with the Golgi reorganization by HCMV 12 , the IGF2R localization to the assembly complex late in infection and the inhibitory effect of its knockout on virus production suggest that HCMV hijacks IGF2R to coordinate cell signaling.…”
Section: Prm Validation Igf2rsupporting
confidence: 79%
“…Previous studies of vIL-6 interactions and activities had identified the direct physical interaction of vIL-6 with VKORC1v2 and gp130, the occurrence of these interactions in the ER compartment, and their contributions to latently infected PEL cell viability and to HHV-8 productive replication in PEL and/or endothelial cell lines (11,(16)(17)(18)24). In the context of PEL cells, vIL-6, VKORC1v2, and vIL-6-VKORC1v2 interactions were associated with regulation of the levels of endogenously expressed CatD (proapoptotic) and IGF2R (proviability/replication) via VKORC1v2-associated promotion of and rescue from ERAD, respectively (19,20). The observed enhanced expression of IGF2R may be effected via VKORC1v2 interaction with calnexin cycle proteins UGGT1 and GlucII to promote protein folding and escape of nascent IGF2R from ERAD and the ER as correctly folded protein (14,36).…”
Section: Discussionmentioning
confidence: 98%
“…5E). In the context of PEL cells, VKORC1v2 was found to associate with pro-CatD and IGF2R, which were regulated negatively and positively, respectively, by vIL-6; these proteins were associated with suppression (CatD) and promotion (IGF2R) of PEL cell viability and productive replication in these cells (20,24). To investigate potential biological activity of VKORC1v2 in iSLK cells, we generated VKORC1v2knockout and control (Cas9 ϩ /gRNA Ϫ ) cell lines (see Materials and Methods).…”
Section: Bindingmentioning
confidence: 94%
See 1 more Smart Citation
“…Upon infection B-lymphocytes induce several impairments of the immune system due to vIL-6 production and the induction of chronic inflammation [51,66,72]. Recently Li et al [73] found that vIL-6, mainly localized in the endoplasmic reticulum, has a pivotal role in viral metabolism, viral lytic replication and enhancement of cell growth. It also contributes to HHV8 infectivity and pathogenesis by the stimulation of cell multiplication and induction of neo-angiogenesis.…”
Section: Hhv8 and Cyclooxygenase: Induction And Suppression Of Immunementioning
confidence: 99%